Épica Barroca : Volume I - O Fiel & O Verdadeiro - Machado, Samir Machado de (2021)
This dissertation is divided into two parts, a historical fiction novel entitled O Fiel e O Verdadeiro, and an essay elaborated in the course of writing, entitled A cartography of O Fiel e O Verdadeiro. The novel follows several characters throughout colonial Brazil beginning on the year 1756, after the Guaranitic War and the earthquake that destroyed Lisbon. Throughout the trajectory of the two protagonists, the young Sofia and Licurgo, a mapping of Brazilian identity is outlined through the fusion of various peoples, religions, rivalries. A first part presents the reality of the southern border through the eyes of Sofia, a 16-year-old girl who lives isolated on her father's farm, in the region that will one day be the city of Porto Alegre. The second part features Licurgo, an 18-year-old soldier who, after being presumed dead, wanders between São Paulo and Minas Gerais like a knight. The third part brings together the two protagonists, and their nuclei of characters, in the city of Rio de Janeiro, and develops plot conflicts that will lead to the following volumes of this project, which propose a tetralogy in four volumes. As for the essay, he addresses the conception and development of this plot, recording the creative path from the many genesis of the idea to its execution, intermingling testimonies of the process, such as accumulation of narrative references, personal and work notes, and reflections on the inherently colonial nature of adventure plots, and how to deal with this structural heritage.